Efektifitas Penerapan Kurikulum Perlebahan dalam Meningkatkan Pengetahuan Masyarakat di Desa Muara Sikabaluan Kepulauan Mentawai - Mardiansyah, Ramos; Eldarni; Hidayati, Abna; Hendri, Nofri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the effectiveness of the application of beekeeping curriculum in improving the knowledge of learning citizens in the honey bee school program in the village of muara sikabaluan, Mentawai Islands. The sample used in this study amounted to 25 people. The research was conducted using one group pretest-posttest method and analyzed using Shapiro-Wilk test and statistical test with paired sample T test. Based on the results of the pretest and posttest, the application of the beekeeping curriculum was able to significantly improve the knowledge and skills of learning citizens with an average of 2.35 to 3.30. Furthermore, based on the results of the paired sample T-test, it is concluded that the beekeeping curriculum has a significant effect on increasing the knowledge of learning citizens. This shows that the beekeeping curriculum has a positive and significant effect on increasing the knowledge and skills of learning citizens. With this increase in knowledge, it is expected that the community will be able to protect the forest area and utilize the forest in developing non-timber forest products (HHBK)